Concurrent sprint and aerobic training in swimming: Influence of exercise sequence on physiological responses and perceived exertion - Nikitakis, I. S.; Bogdanis, G. C.; Paradisis, G. P.; Toubekis, A. G. (Journal of Sports Sciences, 2025)
The study examined the effect of aerobic and sprint sets sequence on physiological responses and perceived exertion during concurrent training sessions. Twelve male highly trained swimmers performed four sessions in randomized order, using combinations of the following training sets: (a) lactate threshold training (8 × 200-m at a speed corresponding to lactate threshold with 30-s recovery; LT), (b) high-intensity aerobic training (8 × 100-m at the maximal aerobic speed with 30-s recovery; MAS) and (c) repeated-sprints training (8 × 25-m repeated sprints with 2-min recovery; SPR). The four combinations used were as follows: LT-SPR, SPR-LT, MAS-SPR, SPR-MAS. Blood lactate (BL), pH, base excess (BE), bicarbonate, heart rate (HR), HR variability, objective [training impulse (iTRIMP)] and subjective training load [session`s rating of perceived exertion (sRPE)] were measured. Between session pH and BE were no different, but mean BL was higher in sessions starting with repeated sprints compared with the reverse order (SPR-LT: 6.3 ± 3.6, LT-SPR: 5.3 ± 3.7 mmol·L-1, p = 0.03; SPR-MAS: 7.2 ± 3.9, MAS-SPR: 6.0 ± 3.7 mmol·L-1, p = 0.05). Bicarbonate in SPR-LT was lower compared with LT-SPR (p = 0.03). sRPE, but not iTRIMP, was higher in sessions starting with SPR compared with the reverse order (p = 0.02). Anaerobic-aerobic set sequence, compared with the reverse order, augments BL response and increases perceived training load but not the training impulse.